Inhibitory effects of oxymatrine on hepatic stellate cells activation through TGF-β/miR-195/Smad signaling pathway - Li-Ying Song; Yu-Tao Ma; Wei-Jin Fang; Yang He; Jia-Li Wu; Shan-Ru Zuo; Zhen-Zhen Deng; Sheng-Feng Wang; Shi-Kun Liu (BMC, 2019)
Abstract Background Oxymatrine (OM), a quinolizidine alkaloid extracted from a herb Sophorae Flavescentis Radix, has been used to treat liver fibrotic diseases. However, the mechanism of its anti-fibrosis effects is still unclear. TGF-β/Smad signaling and miR-195 have been proved to paly an important role in hepatic stellate cells (HSCs) activation and liver fibrosis. In this study, we investigated whether OM could inhibit HSCs activation through TGF-β1/miR-195/Smads signaling or not. Methods First, the effects of OM on HSC-T6 in different concentrations and time points were tested by MTT assay. We choose three appropriate concentrations of OM as treatment concentrations in following experiment. By Quantitative Real-time PCR and Western Blot, then we investigated the effect of OM on miR-195, Smad7 and α-SMA's expressions to prove the correlation between OM and the TGF-β1/miR-195/Smads signaling. Last, miR-195 mimic and INF-γ were used to investigate the relation between miR-195 and OM in HSC activation. Results Our results showed that the proliferation of HSC was significantly inhibited when OM concentration was higher than 200 μg/mL after 24 h, 100 μg/mL after 48 h and 10 μg/mL after 72 h. The IC50 of OM after 24, 48 and 72 h were 539, 454, 387 μg/mL respectively. OM could down-regulate miR-195 and α-SMA (P < 0.01), while up-regulate Smad7 (P < 0.05). In HSC-T6 cells transfected with miR-195 mimic and pretreated with OM, miR-195 and α-SMA were up-regulated (P < 0.05), and Smad7 was down-regulated (P < 0.05) . Conclusions Given these results, OM could inhibit TGF-β1 induced activation of HSC-T6 proliferation in a dose-dependent and time-dependent manner to some extent. We proved that OM inhibited HSC activation through down-regulating the expression of miR-195 and up-regulating Smad7.